Effects of Blue and Red Light On Growth And Nitrate Metabolism In Pakchoi - Fan Xiao-Xue; Xue Feng; Song Bo; Chen Long-Zheng; Xu Gang; Xu Hai (Open Chemistry, 2019)
This study investigated the effects of blue and red light on metabolites of nitrate, key enzymes, and the gene expression of key enzymes in pakchoi plants (Brassica campestris L. var. Suzhouqing). Plants were grown under three light quality treatments, namely, white light (W), red light (R) and blue light (B), at the same photosynthetic photon flux density (PPFD) of approximately 150 μmol m-2 s-1 for 48 hours of continuous illumination, and W was set as the control. The dynamics of net photosynthetic rate in pakchoi subjected to different light treatments were the same as the total chlorophyll contents: blue light > white light > red light. The nitrate reductase (NR) activity, nitrite reductase (NiR) activity, glutamine synthetase (GS) activity and glutamate synthase (GOGAT) activity were highest under blue light. Further, the expression levels of NR, NiR and GS genes were significantly higher under blue light. Under continuous illumination, the auxin content (IAA) in pakchoi leaves was highest under blue light, whereas the abscisic acid (ABA) content was highest under red light. In contrast, there was no significant effect for gibberellin (GA) under any type of light treatment.